Estonia and the refugees: political discourses and artistic representations. Issue 1 (1st January 2017) - Makarychev, Andrey; Yatsyk, Alexandra
ABSTRACT: The article addresses two dimensions of the refugee debate in Estonia – political discourses and cultural representations. The authors specifically focus on distinctions between the mainstream Estonian narrative and that of the Russophone community, as well as on the role of Russia and Europe as two major shapers of the refugee debate